Asymptotically sharp dimension estimates for k-porous sets - Järvenpää, E.; Järvenpää, M.; Käenmäki, A.; Suomala, V. (Mathematica Scandinavica, 2005)
In R^n, we establish an asymptotically sharp upper bound for the upper Minkowski dimension of k-porous sets having holes of certain size near every point in k orthogonal directions at all small scales. This bound tends to n-k as k-porosity tends to its maximum value.